Low-voltage, low-power CMOS arithmetic circuits for energy efficient VLSI applications - Gu, Jiangmin (2008)
We present in this thesis several algorithms and designs, and their IC implementation of low-voltage, low-power CMOS arithmetic circuits for energy efficient VLSI applications. The design methodologies span from circuit level, architecture level to algorithm level.